On Certain Values of the Lvov-Warsaw School and Logical Culture: Towards Challenges of Contemporaneousness - Wybraniec-Skardowska, Urszula (Filozofia Nauki, 2022)
This article explores the question of how the members of the Lvov-Warsaw School promoted values that can be regarded as components of so-called logical culture. The author argues that these values are strictly connected with science. With references to Łukasiewicz, Czeżowski, and Kotarbiński, the article explores how values shape the logical culture and determines society as directed towards values. The article connects the meta-philosophical perspective with the philosophical one.